Role of Astrocytes in Post-traumatic Epilepsy - Xu, Songbai; Sun, Qihan; Fan, Jie; Jiang, Yuanyuan; Yang, Wei; Cui, Yifeng; Yu, Zhenxiang; Jiang, Huiyi; Li, Bingjin (Frontiers in Neurology, 2019)
Traumatic brain injury, a common cause of acquired epilepsy, is a typical to find necrotic cell death within the injury core. The dynamic changes in astrocytes surrounding the injury core contribute to epileptic seizures associated with intense neuronal firing. However, little is known about the molecular mechanisms that activate astrocytes during traumatic brain injury or the effect of functional changes of astrocytes on seizures. In this comprehensive review, we present our cumulated understanding of the complex neurological affection in astrocytes after traumatic brain injury. We approached the problem through describing the changes of cell morphology, neurotransmitters, biochemistry, and cytokines in astrocyte during post-traumatic epilepsy. In addition, we also discussed the relationship between dynamic changes in astrocyte and seizures and the current pharmacologic agents used for treatment. Hopefully, this review will provide a more detailed knowledge from which better therapeutic strategies can be developed to treat post-traumatic epilepsy.